The Relationship between Recruitment and Selection Methods with Human Resource Quality in the Shipping World: A Case Study on PT. Lighthouse Linta Sindo Shipping Company - Andi Nasrun Cahyadi; Syahrir; Andi Arwinda Wildam (LP2M IAIN Palopo, 2025)
The purpose of this study is to analyze the relationship between recruitment and selection methods with the quality of human resources in the shipping world, specifically at PT. Pelayaran Mercusuar Linta Sindo. Data collection methods used were observation, literature study, and interviews. The data analysis used was descriptive qualitative. The results of the study indicate that the recruitment and selection methods to obtain the quality of the company's human resources have been carried out according to predetermined procedures. The requirements for the recruitment method begin with the submission of prospective workers until the ratification of the transfer order and work agreement. The recruitment method is adjusted between the abilities and competencies of job applicants and the company's needs, so that no jobs are filled by people who do not match their abilities and skills. Obstacles encountered in the recruitment method include incomplete applicant certificates and expired certificates, thus hampering the administrative selection or filing process. The recruitment and selection method is to identify areas of improvement and improve the quality of workers.